Pengembangan Aplikasi Pengkoreksi Kekeliruan Pengetikan Kata Berbahasa Hokkien dalam Aksara Latin menggunakan Library Numpy - Richard; Yulius Denny Prabowo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to develop foreign language modeling primarily of Hokkien's language in Latin Acts by using a library of Python named Numpy. Detailing is done based on the manual dictionary manually for this research based on several sources. Detailing is done by entering the Hokkien word to be corrected to compare to the existing word dictionary. The result of this research is a system that can only correct the mistake of writing the Hokkien-speaking word that has only one syllable. And the results of this study can only run through the Python code only.